Theta Burst Stimulation Enhances Connectivity of the Dorsal Attention Network in Young Healthy Subjects: An Exploratory Study - Anderkova, Lubomira; Pizem, Dominik; Klobusiakova, Patricia; Gajdos, Martin; Koritakova, Eva; Rektorova, Irena (Neural plasticity, 2018)
We examined effects of theta burst stimulation (TBS) applied over two distinct cortical areas (the right inferior frontal gyrus and the left superior parietal lobule) on the Stroop task performance in 20 young healthy subjects. Neural underpinnings of the behavioral effect were tested using fMRI. A single session of intermittent TBS of the left superior parietal lobule induced certain cognitive speed enhancement and significantly increased resting-state connectivity of the dorsal attention network. This is an exploratory study that prompts further research with multiple-session TBS in subjects with cognitive impairment.
Keywords: dospělí; Healthy Volunteers; Female; Psychomotor Performance; Theta Rhythm; pozornost; nervová síť; Adult; mladý dospělý; ženské pohlaví; zdraví dobrovolníci pro lékařské studie; Attention; lidé; psychomotorický výkon; transkraniální magnetická stimulace; Nerve Net; Male; Young Adult; Parietal Lobe; Stroopův test; temenní lalok; theta rytmus EEG; Transcranial Magnetic Stimulation; Random Allocation; Stroop Test; mužské pohlaví; náhodné rozdělení; Humans